Sample rating in water-alcohol technology by profile non-linear quality criteria - Koretska, Iryna; Kuzmin, Oleg; Zinchenko, Tetiana (My University, 2020)
The purpose of the article is to create a mathematical model for the determination of rational recipe compositions based on water-alcohol infusions of vegetable raw materials for the technology of restaurant products. The task of the research was to substantiate the method of ranks with the use of sensory evaluation of samples of water-alcohol infusions in the restaurant products technology. Метою роботи є створення математичної моделі для визначення раціональних рецептурних композицій на основі водно-спиртових настоїв рослинної сировини для технології ресторанної продукції. Завданням дослідження було обґрунтування методу рангів із застосуванням сенсорного оцінювання зразків водно-спиртових настоїв у технології ресторанної продукції.
Keywords: кафедра технології ресторанної і аюрведичної продукції; кафедра вищої математики імені проф. Можара В. І.; ресторанна продукція; водно-спиртові настої; оцінка якості; рейтинг зразків; restaurant products; water-alcohol infusions; quality assessment; sample rating